Single-Stage Quadruple Valve Replacement with Mechanical and Bioprosthetic Valves: An 8-Year Follow-up Study from India - Gera, Akriti; Misri, Amit; Bajpai, Pankaj; Sharma, Rajesh; Bhan, Anil (The Thoracic and Cardiovascular Surgeon Reports, 2025)
Congenital heart disease, repaired or unrepaired, requires lifelong follow-up. Carcinoid disease, rheumatic heart disease, and infective endocarditis can damage all four cardiac valves. Multiple valve replacement has a poor outcome.A 23-year-old male underwent single-stage quadruple valve (mechanical [mitral and aortic] and bioprosthetic [tricuspid and pulmonary]) replacement due to rheumatic carditis and surgical complications. Over 8 years of follow-up, he is asymptomatic, has no prosthetic valve-related complications, and has improved cardiac function.Single-stage quadruple valve replacement with mechanical and bioprosthetic valves has a good long-term outcome. To the best of our knowledge, this is the longest follow-up study from India.
Keywords: quadruple valve replacement; rheumatic carditis; TOF